Acetyl‐coenzyme A carboxylase alpha promotion of glucose‐mediated fatty acid synthesis enhances survival of hepatocellular carcinoma in mice and patients. Issue 4 (19th February 2016) - Wang, Ming‐Da; Wu, Han; Fu, Gong‐Bo; Zhang, Hui‐Lu; Zhou, Xu; Tang, Liang; Dong, Li‐Wei; Qin, Chen‐Jie; Huang, Shuai; Zhao, Ling‐Hao; Zeng, Min; Wu, Meng‐Chao; et al.
Abstract : Solid tumors often suffer from suboptimal oxygen and nutrient supplies. This stress underlies the requirement for metabolic adaptation. Aberrantly activated de novo lipogenesis is critical for development and progression of human hepatocellular carcinoma (HCC). However, whether de novo lipogenesis influences biological behaviors of HCCs under conditions of metabolic stress are still poorly understood. Here, we show that HCCs display distinct levels of glucose‐derived de novo lipogenesis, which are positively correlated with their survival responses to glucose limitation. The enhanced lipogenesis in HCCs is characterized by an increased expression of rate‐limiting enzyme acetyl‐coenzyme A carboxylase alpha (ACCα). ACCα‐mediated fatty acid (FA) synthesis determines the intracellular lipid content that is required to maintain energy hemostasis and inhibit cell death by means of FA oxidation (FAO) during metabolic stress. In accord, overexpression of ACCα facilitates tumor growth. ACCα forms a complex with carnitine palmitoyltransferase 1A (CPT1A) and prevents its mitochondria distribution under nutrient‐sufficient conditions. During metabolic stress, phosphorylation of ACCα leads to dissociation of the complex and mitochondria localization of CPT1A, thus promoting FAO‐mediated cell survival. Therefore, ACCα could provide both the substrate and enzyme storage for FAO during glucose deficiency. Up‐regulation of ACCα is also significantly correlated with poorer overall survival and disease recurrence postsurgery. Multivariate Cox's regression analysis identified ACCα as an effective predictor of poor prognosis. Conclusion: These results present novel mechanistic insight into a pivotal role of ACCα in maintaining HCC survival under metabolic stress. It could be exploited as a novel diagnostic marker and therapeutic target. (Hepatology 2016;63:1272–1286)